Preventing crime: a holistic approach - Bjørgo, Tore (Crime prevention and security management, 2016)
Introduction: a comprehensive model for preventing crime -- Domestic burglary -- Violent youth gangs -- Organised crime originating from outlaw motorcycle gangs -- Driving under the influence -- Terrorism -- The way forward: some concluding comments on application and evaluation